SURVEY OF A FUNCTIONAL STATE OF MASSETER MUSCLES IN EDENTELOUS PATIENTS BASED ON THE DATA OF SURFACE ELECTROMYOGYOPHY STUDIES - V.S. Kuz; V.M. Dvornyk; G.M. Kuz; G.M. Balya; O.S. Shemetov (Український стоматологічний альманах)
The difficulty of prosthetics and rehabilitation of patients with complete loss of teeth is associated with a burdened psychological and anatomical status. The main reasons for teeth extractions are periodontal tissue diseases, diseases of hard tooth tissues of carious and non-carious origin and traumas. Complete loss of teeth leads to a large number of local and general complications. The masticatory apparatus undergoes a number of functional and morphological changes. It becomes necessary to manufacture complete removable dentures to prevent the occurrence of pathologies in such situations. The effectiveness at this type of dentures depends on compliance with the protocols of their fabrication and the quality of the basic dental materials. Currently, prosthodontists use thermoplastic plastics in the fabrication of complete removable prostheses, more commonly the main group of materials for this constructions are heat-polymerized acrylic resins. Evaluation of the quality of the fabricated complete removable dentures and of the functional state of the masticatory system after prosthetics is determined by their fixation and stabilization, restoration of the patient's appearance and degree of masticatory effectiveness. It can be determined by using of a surface electromyography an objective method for evaluation of the functional state of muscles by recording of their electrical biopotentials.